2015
DOI: 10.1161/atvbaha.115.305278
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine Dimethylaminohydrolase 2 Regulates Nitric Oxide Synthesis and Hemodynamics and Determines Outcome in Polymicrobial Sepsis

Abstract: Objective— Nitric oxide is a key to numerous physiological and pathophysiological processes. Nitric oxide production is regulated endogenously by 2 methylarginines, asymmetric dimethylarginine (ADMA) and monomethyl- l -arginine. The enzyme that specifically metabolizes asymmetric dimethylarginine and monomethyl- l -arginine is dimethylarginine dimethylaminohydrolase (DDAH). The first isoform dimethylarginine dimethylaminohydrola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 29 publications
(30 reference statements)
6
42
2
Order By: Relevance
“…[72] Recent data from mice with impaired ADMA metabolism point in the same direction. [73] As expected, slight differences between studies were observed, with slightly smaller effects being reported in studies of higher quality (higher number of events, longer duration of followup and higher number of included confounders in the statistical analysis). In addition, associations were slightly stronger for studies that measured ADMA in plasma compared to studies measuring it in the serum.…”
Section: Discussionsupporting
confidence: 53%
“…[72] Recent data from mice with impaired ADMA metabolism point in the same direction. [73] As expected, slight differences between studies were observed, with slightly smaller effects being reported in studies of higher quality (higher number of events, longer duration of followup and higher number of included confounders in the statistical analysis). In addition, associations were slightly stronger for studies that measured ADMA in plasma compared to studies measuring it in the serum.…”
Section: Discussionsupporting
confidence: 53%
“…We postulate that this is one of the mechanisms by which animals deficient in DDAH2 demonstrate impaired monocyte function and elevated mortality in animal models of sepsis 31 and may in part explain the association between polymorphisms of the human DDAH2 gene and outcome in patients with septic shock 38 This study also highlights differing mechanisms in the synthesis of NO across species. In our murine studies, elevated iNOS was observed in isolated hypoxic primary murine macrophages consistent with previous studies of the impact of hypoxia on the inducible isoform of the enzyme 39 .…”
Section: Discussionmentioning
confidence: 84%
“…This suggests that DDAH2 regulation in hypoxia may be tissue specific and reflect differing adaptive responses to hypoxic stress. We have previously shown that global and macrophage specific knockout of DDAH2 in murine models of severe sepsis leads to a significant excess mortality which is mediated by impaired macrophage phagocytosis, bactericidal ability and NO synthesis 31 . Sepsis is a complex physiological insult in which multiple processes contribute to organ dysfunction and death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations